Téseras y monedas. Iconografía zoomorfa y formas jurídicas de la Celtiberia (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
If we compare the zoomorphic images in Celtiberian coins with the form of some bronze tesserae, we easy can establish an iconographic relation. This ressemblance seems to prove the existence of animal images linked to the divinities that guarded pacts. The use of these animal images in coins could be an identification of the figure in the observe  with a divinity. This way, Celtiberian coins would have a place for the divine image (observe) and another one for the political power of  the  elite (reverse).